La theorie interpretative: a-t-elle un apport a la pedagogie de traduction ? (2023)
This paper explores the evolution of the interpretative theory of translation, transitioning from its hermeneutic roots to emphasising a profound understanding of the source message, This theory redefines translation by prioritising the reservation of meaning beyond literal reproduction. Under this perspective, translation becomes a complex act of comprehension, deverbalisation and reverbalisation, positioning translators as facilitators of understanding beyond linguistic barriers. The article extends principles of interpretative theory to translator training and discusses tangible implications for translation students. By identifying potential challenges, the article provides a brief outlook on the future direction of this theoretical evolution, thereby positioning translation at the heart of communication exchanges as a dynamic and reflexive pedagogical subject. In sum, it offers a comprehensive exploration of this theoretical evolution, shedding light on its impact on translation practice and emphasising its central role in translation training